Impact of productive social safety net on households' vulnerability to food insecurity in Tanzania - Basil Msuha; Luitfred D. Kissoly (Cogent Economics & Finance, 2024)
The effectiveness of social safety nets (SSNs) as anti-poverty policy instruments is increasingly attracting attention in development discourse. Previous studies on their impacts have mainly considered outcomes other than vulnerability, leaving a gap in the knowledge and literature. We use the Tanzanian 2017-18 Household Budget Survey dataset, comprising 9,463 households, to evaluate the impact of the productive social safety net (PSSN) program on households' vulnerability to food insecurity (VFI). The VFI is evaluated using the vulnerability as expected poverty (VEP) approach, whereas the impact is estimated using the Instrumental Variable (IV) approach. We found evidence consistent with the significant impact of PSSN on the VFI. Curiously, the estimated impacts are greater for households enrolled in conditional cash transfer (CCT) and public works (PW) combined, implying that a package of CCT and PW is likely to have a greater impact on vulnerability reduction space. Overall, the results provide evidence in support of policies that encourage wider expansion of SSNs as a policy instrument for assisting extremely poor households in moving out of the chronically poor and the risk of falling or remaining food insecure in the future. Social safety nets are widely used in sub-Saharan Africa to address persistent poverty. However, despite holding the premise of poverty and vulnerability reduction, opponents criticize them as short-term measures and wasteful use of limited public resources, with an insignificant impact on poverty reduction. Previous research has primarily concentrated on evaluating ex post evidence, with little attention given to ex ante evidence. Both types of evidence are crucial for determining the effectiveness of anti-poverty policy interventions because poverty is a dynamic phenomenon that can change over time. We drew on the Tanzanian 2017-18 Household Budget Survey dataset, comprising 9,463 households, to evaluate the impact of the productive social safety net (PSSN) program on households' vulnerability to food insecurity, considering the role of conditional cash transfer (CCT) and public works (PW) schemes in the vulnerability reduction space. The vulnerability to food insecurity is estimated using vulnerability as expected poverty, whereas the impact is estimated using the instrumental variable (IV) approach. Findings indicated that social safety nets significantly reduced households' vulnerability to food insecurity, with CCT and PW combined having more impact than CCT alone. The findings imply that social safety nets are effective in reducing poverty and vulnerability, and combining CCTs and PWs may have a significantly greater impact than when the two are separated. Consequently, it is quite shortsighted to view social safety nets as merely short-term palliatives, wasting money or squandering scarce public resources, and doing little to overcome the problems of poverty and food insecurity. The significance of this study lies in its endeavor to broaden the range of existing literature on the effectiveness of social safety nets by incorporating ex ante analysis. This knowledge and understanding are helpful in expanding or designing effective social safety nets.
Keywords: 330; Productive social safety net; conditional cash transfers; public works; vulnerabilityas expected poverty; vulnerability to foodinsecurity; instrumental variable; Tanzania